ON THE IMPORTANCE OF MONOGENEAN HELMINTHES IN BRAZILIAN CULTURED NILE TILAPIA - Gonçalves, Eduardo L.T. (2009)
There's still a lot of ongoing debate whether the correct taxonomical nomenclature should be Monogenea or Monogenoidea. In this current note it will be addressed as Monogenea, since it's the most traditional (Wheeler & Chisholm, 1995), and therefore most known nomenclature. But the authors would like to point that we support the use of Monogenoidea for its phylogenetic approach.